Kedudukan, Peran, dan Fungsi Dukun Pandita di Suku Tengger - Syifa Sakinah Hidayat (Umbara, 2019)
Tengger community in Ngadisari village maintains its values and tradition. One of it is the traditional ceremony led by Dukun Pandita. This study aims at describing the role, function, and leadership system of Dukun Pandita as part of the large social structure of the Tenggerese community of Ngadisari. This study applies qualitative method. Data were collected through in-depth interviews, participation observations, and secondary data collection. This study finds that Dukun Pandita has responsibilities and duties related to religious ritual and adat. He holds a crucial position in this context, and therefore his role and function in religious ceremonies is central, sacred, and pure; and his authority is charismatic.